1998
DOI: 10.1177/019459989811800510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Oral Antiseptic Rinses on Bacterial Counts of Saliva in Healthy Human Subjects

Abstract: Wound infections remain a significant source of morbidity in patients undergoing major head and neck operations that invade the aerodigestive tract. Infection rates have been significantly reduced by the administration of perioperative intravenous antibiotics; however, the incidence of infection remains unacceptably high. This study was undertaken to help identify an oral antiseptic that could significantly reduce the bacterial colony count of human saliva. A randomized, prospective clinical trial was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…However, the specific retake timing needs further consideration with respect to the substantivity of mouthwashes in the oral cavity. Research has demonstrated [54][55][56] that 0.2% CHX has the highest substantivity values when compared with the values of other commercial mouthwashes. A period of 3-12 h is required for 0.2% CHX to be washed out of the mouth [9,57].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific retake timing needs further consideration with respect to the substantivity of mouthwashes in the oral cavity. Research has demonstrated [54][55][56] that 0.2% CHX has the highest substantivity values when compared with the values of other commercial mouthwashes. A period of 3-12 h is required for 0.2% CHX to be washed out of the mouth [9,57].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Apart from its antiplaque and antigingivitis activity, CHX is therefore also particularly effective for the prevention of infectious complications of oral origin. [5][6][7] However, up to now, we have not found any protocol for the administration of CHX which specifies the most effective dose in those clinical situations in which strong antibacterial activity is required; this is probably due to the absence of scientific evidence based on microbiological and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In the majority of published series, measurement of the CHX antimicrobial activity in saliva has been performed using j o u r n a l o f d e n t i s t r y 3 8 ( 2 0 1 0 ) 5 4 1 -5 4 6 a r t i c l e i n f o Article history: plate culture microbiological techniques. [1][2][3][4] However, the reliability of these techniques is questionable, and fluorescence methods using specific fluorochromes to identify viable and non-viable bacteria have been proposed as alternatives. 17,18 In a recent study, we have demonstrated that epifluorescence microscopy using the SYTO 9/propidium iodide dual stain (LIVE/DEAD 1 BacLight TM ) was an effective method for quantifying the antibacterial activity of CHX on salivary flora in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorhexidine appears to be a reasonable choice for maintaining good oral hygiene to reduce plaque and salivary levels of bacteria by up to 85% [23]. Transfer of group B Streptococcus from mother -infant during parturism is reduced due to the usage of chlorhexidine gluconate [24].…”
Section: Selective Digestive Decontamination (Sdd)mentioning
confidence: 99%